Respuesta :
For this case we have the following function:
p (x) = - 2x ^ 2 + 40x-72
We must equal the function to zero:
-2x ^ 2 + 40x-72 = 0
We now look for the roots of the polynomial, for this, we rewrite:
x ^ 2-20x + 36 = 0
Factoring we have:
(x-18) * (x-2) = 0
The roots are:
x1 = 2
x2 = 18
Answer:
lower temperature: 2 degrees celsius
higher temperature: 18 degrees celsius
p (x) = - 2x ^ 2 + 40x-72
We must equal the function to zero:
-2x ^ 2 + 40x-72 = 0
We now look for the roots of the polynomial, for this, we rewrite:
x ^ 2-20x + 36 = 0
Factoring we have:
(x-18) * (x-2) = 0
The roots are:
x1 = 2
x2 = 18
Answer:
lower temperature: 2 degrees celsius
higher temperature: 18 degrees celsius